Managing geography learning objects using personalized project spaces in G-Portal - GOH, Dion Hoe-Lian (Institutional Knowledge at Singapore Management University, 2005)
The personalized project space is an important feature in G-Portal that supports individual and group learning activities. Within such a space, its owner can create, delete, and organize metadata referencing learning objects on the Web. Browsing and querying are among the functions provided to access the metadata. In addition, new schemas can be added to accommodate metadata of diverse attribute sets. Users can also easily share metadata across different projects using a “copy-and-paste” approach. Finally, a viewer to support offline viewing of personalized project content is also provided.